The Impact of Social Media Strategies of Non-Profit Organizations on Covid-19 Donation Intention in Indonesia - Utomo, Dutho Suh; Paoprasert, Naraphorn; Yousuk, Ramidayu (Universitas Semarang, 2022)
Introduction: When a disaster strikes, non-profit organizations working in the field of donations will be beneficial, as their role is to raise funds and direct them toward disaster recovery. A large number of internet and social media users in Indonesia provides opportunities for non-profit organizations to use social media strategies in fundraising promotions. Therefore, this study examined the relationship between non-profit organization strategies on social media such as interactivity and disclosure, as well as transaction safety in influencing the intention to donate in the Covid-19 case in Indonesia. The non-profit organization in this study was a non-profit organization that raised funds through social media for Covid-19 assistance. Social media in this study was not specific to one platform, but to Instagram and Facebook users who know the non-profit organization.Methods: The study was conducted on Indonesians who have social media accounts and know about the social media of non-profit organizations that were raising funds for Covid-19.Findings: The study found that interactivity, disclosure, and transaction safety influenced the intention to donate through trust mediation. However, these factors have no direct impact on donation intention. Therefore, trust is an important factor in implementing social media strategies for non-profit organizations because it is the full mediator in this case.Originality: This study was novel in that it examined the effect of social media strategy on intention to donate, taking into account the perception of payment safety, specifically for the promotion of Covid-19 fundraising through social media by non-profit organizations in Indonesia.